The Effect of Memrise Application on Student’s Vocabulary Mastery at the Tenth Grade of SMKN 4 Bone - Yardina Ulfaeni; Gunawan; Andi Achmad Dahlan (PT FORMOSA CENDEKIA GLOBAL, 2025)
Vocabuary mastery is one of the factors to master English as foreign language. The mastery of English vocabulary itself is closely related to the ability of the learner in acquiring the vocabulary. This study looks at how students' vocabulary enrichment is affected when they use the Memrise app as a learning media. Using a non-equivalent group model and a quasi-experimental methodology, this study employs a quantitative approach in the tenth grade of SMKN 4 Bone. Where this research involving two groups; an experimental class (X MPLB) utilizing the Memrise application and a control class (X TKJ) not using the Memrise application. This research aims to determine whether the use of the Memrise application enhances vocabulary mastery among students. Pre-test and post-test were administrated to measure vocabulary proficiency. Since the significant value (Sig 2 tailed) is 0.117 > 0.05, it may be concluded from the results that H0 is accepted and H1 is rejected in the independent sample t-test